2009
DOI: 10.1007/s10571-009-9457-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of IGF-I Following Kainic Acid-Induced Hippocampal Degeneration in the Rat

Abstract: Insulin-like growth factor I (IGF-I) has been shown to act as a neuroprotectant both in in vitro studies and in in vivo animal models of ischemia, hypoxia, trauma in the brain or the spinal cord, multiple and amyotrophic lateral sclerosis, Alzheimer's and Parkinson's disease. In the present study, we investigated the neuroprotective potential of IGF-I in the "kainic acid-induced degeneration of the hippocampus" model of temporal lobe epilepsy. Increased cell death--as detected by FluoroJade B staining--and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…This hypothesis was supported by animal model studies which showed that IGF-1 supplement prevented the loss of dopaminergic neurons [11]. In an AD model, IGF-1 also showed a protective effect on hippocampus degeneration [12], further supporting the protective role of IGF-1 in neurodegenerative diseases. However, we did not find any change of plasma IGF-1 in ET patients in our study.…”
Section: Discussionmentioning
confidence: 84%
“…This hypothesis was supported by animal model studies which showed that IGF-1 supplement prevented the loss of dopaminergic neurons [11]. In an AD model, IGF-1 also showed a protective effect on hippocampus degeneration [12], further supporting the protective role of IGF-1 in neurodegenerative diseases. However, we did not find any change of plasma IGF-1 in ET patients in our study.…”
Section: Discussionmentioning
confidence: 84%
“…These possible mechanisms include the superior calcium-handling capacity of CA2 pyramidal neurons compared with that of neurons in other CA areas 68 and the high expression levels of molecules associated with neuroprotection, such A1Rs 77,111 and receptors and binding partners for growth factors, which have been shown to promote neuronal survival and reduce seizure activity in animal models 112,113 . Indeed, local administration of insulin-like growth factor 1 (IGF1) has been shown to reduce seizure severity and decrease neuronal loss in animal and cell culture models of epilepsy 114,115 , which may be attributable to the high expression levels of the IGF1 receptor and IGF-binding protein 4 in rodent CA2 neurons 116,117 . In addition, somatostatin receptor 5, which negatively couples to voltage-gated calcium channels, is highly expressed in CA2 neurons, as shown in gerbils 118 , and may contribute to protection of CA2 neurons from insults that trigger calcium influx.…”
Section: Resistance To Injurymentioning
confidence: 99%
“…Overall, GH, GHSs, like ghrelin and cognate molecules, and IGF-1 have been found to exert neuroprotective effects in different models [306, 307], including kainate-induced SE [308, 309], the pilocarpine model [310], cerebral ischemia [311, 312], and models of neurodegenerative diseases [313]. Notably, rats in which IGF-1 was administered intracerebrally together with kainate, no signs of degeneration were detected in the contralateral hemisphere, whereas ipsilateral cell loss, assessed by Fluoro-Jade B staining, was consistently reduced, in association with less reactive gliosis [314].…”
Section: Neuroprotectionmentioning
confidence: 99%